The reality of the level of arbitration in Iraq for two seasons 2006-2005 / 2007-2006 - Qasem, Sabah (Journal of Physical Education, 2008)
With all caraway seasonal often mention the mass media role arbitration negative to production the team to no good the level of referees' performance football and to from research someone the International referee the researcher decided to study the problems principal to weaken the level of referee to Iraq season 20052006-20062007 and choose medium replacement to ascend to level of referees and to elaborate to good level football therefore to be complete division application special to players and coaches and referees to method at random and respond to question (121)players and(19)coaches and(42)referees to be total division (182) representation percentage 25% to society original.